Respuestas

2012-11-28T03:46:24+01:00

este es el segundo el que es por el m. de igualacion

en 1 y 2 despejar x                                            3=4

3.- x=8-2y                                                   8-2y = 11-2y

          2                                                         2         3

4.-x=11-2y                                              24-6y=22-4Y

         3                                                  -6y+4y=22-24

                                                               -2y=-2

                                                                y=1

reemplazar y en 3

x=8-2(1)

     2


x=3